Digital PCR: A Sensitive and Precise Method for KIT D816V Quantification in Mastocytosis. (1st March 2018) - Greiner, Georg; Gurbisz, Michael; Ratzinger, Franz; Witzeneder, Nadine; Simonitsch-Klupp, Ingrid; Mitterbauer-Hohendanner, Gerlinde; Mayerhofer, Matthias; Müllauer, Leonhard; Sperr, Wolfgang R; Valent, Peter; Hoermann, Gregor
Abstract: BACKGROUND: The analytically sensitive detection of KIT D816V in blood and bone marrow is important for diagnosing systemic mastocytosis (SM). Additionally, precise quantification of the KIT D816V variant allele fraction (VAF) is relevant clinically because it helps to predict multilineage involvement and prognosis in cases of advanced SM. Digital PCR (dPCR) is a promising new method for sensitive detection and accurate quantification of somatic mutations. METHODS: We performed a validation study of dPCR for KIT D816V on 302 peripheral blood and bone marrow samples from 156 patients with mastocytosis for comparison with melting curve analysis after peptide nucleic acid-mediated PCR clamping (clamp-PCR) and allele-specific quantitative real-time PCR (qPCR). RESULTS: dPCR showed a limit of detection of 0.01% VAF with a mean CV of 8.5% and identified the mutation in 90% of patients compared with 70% for clamp-PCR ( P < 0.001). Moreover, dPCR for KIT D816V was highly concordant with qPCR without systematic deviation of results, and confirmed the clinical value of KIT D816V VAF measurements. Thus, patients with advanced SM showed a significantly higher KIT D816V VAF (median, 2.43%) compared with patients with indolent SM (median, 0.14%; P < 0.001). Moreover, dPCR confirmed the prognostic significance of a high KIT D816V VAF regarding survival ( P < 0.001). CONCLUSIONS: dPCR for KIT D816V provides a high degree of precision and sensitivity combined with the potential for interlaboratory standardization, which is crucial for the implementation of KIT D816V allele burden measurement. Thus, dPCR is suitable as a new method for KIT D816V testing in patients with mastocytosis.